White Photoluminescent Ti3C2 MXene Quantum Dots with Two‐Photon Fluorescence. Issue 9 (10th March 2019) - Lu, Siyu; Sui, Laizhi; Liu, Yuan; Yong, Xue; Xiao, Guanjun; Yuan, Kaijun; Liu, Zhongyi; Liu, Baozhong; Zou, Bo; Yang, Bai
Abstract: A recently created class of inorganic 2D materials, MXenes, has become a subject of intensive research. Reducing their dimensionality from 2D to 0D quantum dots (QDs) could result in extremely useful properties and functions. However, this type of research is scarce, and the reported Ti3 C2 MXene QDs (MQDs) have only shown blue fluorescence emission. This work demonstrates a facile, high‐output method for preparing bright white emitting Ti3 C2 MQDs. The resulting product is two layers thick with a lateral dimension of 13.1 nm. Importantly, the as prepared Ti3 C2 MQDs present strong two‐photon white fluorescence. Their fluorescence under high pressure is also investigated and it is found that the white emission is very stable and the pressure makes it possible to change from cool white emission to warm white emission. Hybrid nanocomposites are then fabricated by polymerizing Ti3 C2 MQDs in polydimethylsiloxane (PDMS) solution, and the bright white emitting hybrid materials in white light‐emitting diodes are used. This work provides a facile and general approach to modulate various nanoscale MXene materials, and could further aid the wide development of applications for MXene materials in various optical‐related fields. Abstract : A facile, high‐output method for the fabrication of Ti3 C2 MXene quantum dots (MQDs) with direct white photoluminescence and two‐photon fluorescence is unprecedentedly designed. High‐pressure studies of Ti3 C2 MQDs are also performed, demonstrating a stable white emission that changes from cool white emission to warm white emission. The work paves a general way to achieve nanoscale MXene materials with enhanced applications in various optical‐related fields.